2010
DOI: 10.1007/s00198-010-1197-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of low doses of pamidronate in osteopenic patients administered in the early post-renal transplant

Abstract: A low dose of pamidronate prevents bone loss in osteopenic patients when administered immediately after RT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 16 publications
(21 reference statements)
0
36
0
1
Order By: Relevance
“…However, treatment is well tolerated in kidney transplant recipients with a GFR.30 ml/min per 1.73 m 2 , with no significant adverse effects compared with placebo/no treatment (30). The key RCTs using bisphosphonates in kidney transplant recipients are summarized in Table 2 (41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52). Most of the studies show that bisphosphonate therapy preserves or increases BMD in the lumbar spine and femoral neck in the early post-transplantation period.…”
Section: Antiresorptive Agentsmentioning
confidence: 99%
“…However, treatment is well tolerated in kidney transplant recipients with a GFR.30 ml/min per 1.73 m 2 , with no significant adverse effects compared with placebo/no treatment (30). The key RCTs using bisphosphonates in kidney transplant recipients are summarized in Table 2 (41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52). Most of the studies show that bisphosphonate therapy preserves or increases BMD in the lumbar spine and femoral neck in the early post-transplantation period.…”
Section: Antiresorptive Agentsmentioning
confidence: 99%
“…In previous studies, transplant recipients who were taking calcium and vitamin D achieved significantly increased BMD at the lumbar spine and femoral neck, no bone loss at the proximal femur, and decreased PTH levels compared with patients taking calcium alone or placebo [7,24]. Early bisphosphonate therapy after transplantation prevented bone loss and improved BMD, regardless of the type of bisphosphonates used, including pamidronate, alendronate, ibandronate, zoledronate, and risedronate [25][26][27][28][29]. A metaanalysis of 11 randomized controlled trials that employed bisphosphonates or active vitamin D analogues revealed that there was an increase in BMD and a significant reduction in the risk of fractures [30].…”
Section: Prevention and Treatmentmentioning
confidence: 90%
“…In a larger, more recent study of kidney transplant recipients treated with pamidronate at months 0, 1, 4, 8, and 12, Walsh et al found that BMD improved at the LS and remained stable at the FN at 1 year in treated patients compared to controls, who had substantial losses [282]. Less frequent dosing of pamidronate (at 0 and 3 months) in renal transplant recipients reduced bone loss at the spine but not the hip in one study [283]. Aris et al, in a 2-year randomized, controlled but nonblinded trial, demonstrated that intravenous pamidronate (30 mg every 3 months) was associated with an 8% increase in both spine and hip BMD in patients who underwent lung transplantation for CF [273].…”
Section: Intravenous Pamidronatementioning
confidence: 92%
“…Intravenous pamidronate administered in repeated doses prevented bone loss at the LS and FN in kidney [271,281,283], heart [274,279], liver [284,285] and lung [273,278] transplant recipients. In a small, open but randomized clinical trial, intravenous pamidronate was administered to kidney transplant recipients at time of grafting and again 1 month later [270], completely preventing LS and FN bone loss, which fell by 6% (LS) and 9% (FN) in controls.…”
Section: Intravenous Pamidronatementioning
confidence: 97%